Structural characterization and antioxidant activity of pectic polysaccharides from Veronica peregrina L. - Yan, Su; Liu, Xianbin; Wang, Yuwen; Yang, Xiaomin; Bai, Lu; Sun, Lin; Zhou, Yifa; Cui, Sisi (Frontiers in Nutrition, 2023)
Background Pectins are a class of acidic polysaccharides with complex structures. Different pectin molecules are composed of different domains, which have an important impact on their biological activity. Objective This study aimed to determine the structural features and the antioxidant activities of the pectic polysaccharides isolated from Veronica peregrina L. Methods The polysaccharide was isolated from Veronica peregrina L by water extraction and fractionated by ion exchange chromatography and gel permeation chromatography. The structure features of the pectic polysaccharides were determined by Fourier transforminfrared spectroscopy (FT-IR) and Nuclear magnetic resonance (NMR). The antioxidant activities was evaluated by the DPPH, OH and ABTS radical scavenging ability. Results WVPP-A2b and WVPP-A3b, with molecular weights of 48.7 × 104 and 77.6 × 104 kDa, respectively, contained homogalacturonan (HG), rhamnogalacturonan I (RG-I), and rhamnogalacturonan II (RG-II) domains with a mass ratio of 2.08:2.64:1.00 and 3.87:4.65:1:00, respectively. The RG-I domain contained an arabinogalactan II backbone and arabinans consisting of t-Araf, (1→5)-α-Araf, and (1→3,5)-α-Araf. WVPP-A3b also contained short chains consisting of the [t-Araf-(1→5)-α-Araf-(1→] structural unit. WVPP-A3b showed stronger ability to scavenge DPPH, hydroxyl, and ABTS radicals, which was potentially associated with its high content of galacturonic acid and presence of the HG domain. Conclusion The results provide information for enhancing knowledge of the structureactivity relationship of pectic polysaccharides from V. peregrina and their potential application in the healthcare food field.